A REVIEW ON EFFICIENCY OF ARTIFICIAL INSEMINATION IN CATTLE BREEDING IN ETHIOPIA - Mekonnen, Teweldemedhn; Meseret, Selam (Bangladesh Journal of Multidisciplinary Scientific Research, 2023)
Ethiopia has a large cattle and small ruminant population in Africa. Livestock production provided approximately 35 to 49% of the total agricultural GDP of Ethiopia. However, the commercialization of livestock genetic resources in the country is almost none. This review aims to present the application and efficiency of Artificial Insemination (AI) in cattle and small ruminants in Ethiopia. A bull is limited to less than 100 mating per year; however, a dairy sire, through AI, can provide semen for more than 60,000 services in one year. AI service in cattle was widely practised. The output of decades of crossbreeding programmes in Ethiopia through AI was relatively insignificant because the exotic breeds and their crossbreds account for about 1.44%. Applying AI service to small ruminants in Ethiopia is not a common practice except for a few ignitions. Conventional AI breeding indicated that the number of services per conception (NSC) ranged from 1.14 in local cows to 2.47 in different cows’ genotypes under other management systems. The conception rate at first insemination (CR1) ranged from 7.14% in different genotypes of cows up to 75.5% in crossbred dairy cows kept under extensive and intensive management systems. Estrus synchronization followed AI breeding indicated that CR1 ranged from 24.69% in 95.8% of Zebu cows up to 70.6% in Boran cows kept under a semi-intensive management system. Strategic interventions for AI efficiency improvement should be identified and practised. Conventional AI breeding and estrus synchronization followed by AI breeding should be practised in small ruminant breeding in Ethiopia.